China mascots evolution of Asian games from 1990-2023: on cultural meaning and visual correlation - Cheng, Wen Yi; Abdul Razak, Mohamed Razeef; Wang, Yun Long (Faculty of Art and Design, 2025)
International sports events are conducive to expanding the influence of the host country and city, improving the host city's popularity and the town's humanistic quality. In the context of frequent international cultural exchanges, As an intuitive and easy-to-understand form of publicity, sports mascots must reflect national characteristics and cater to the development of the current era. It meets the spread of cultural business concepts and people's emotional needs. The Asian Games is a sports event that reflects the level of sports among Asian countries, the spirit of unity and cultural exchanges among the people of Asian countries. Since 1990, China has hosted the Asian Games three times. The 11th Beijing Asian Games in 1990 was the first comprehensive international sports event independently held after the founding of New China. In 2010, the 16th Asian Games was held in Guangzhou. The 19th Asian Games was held in Hangzhou in September 2023. The successful hosting of many international sports events in China has made sports mascot design a hot topic of social concern. There is no research on mascot design development and cultural relevance for the Asian Games in China. This study examines the evolution of mascot design for the China Asian Games from 1990 to 2023. It explores it from three aspects: visual expression form, cultural function, and development trends of the times. The purpose is to explore the evolution in the visual design and cultural relevance of the mascots of the Chinese Asian Games in different locations and periods. This study adopted situational analysis and visual analysis. Qualitative research was conducted through literature review, analysis of mascots based on Bass semiotics, and semi-structured interviews to obtain data. The study found that China held the Asian Games thrice in Beijing, Guangzhou, and Hangzhou. The mascots' design elements came from the host cities' unique culture and urban development. The three mascots were created at different times. The visual representation represents the social development of China in different periods. This study provides a corresponding reference for future Chinese sports mascot design decisions. Chinese sports mascot design research needs to explore the impact of developing Chinese sports mascot design.